The Directorial Treatment of Socially Forbidden Topics in Television series (Al-Academy, 2025)
Television drama is considered one of the expressive mediums that have a direct impact on the viewer due to its depiction of reality through significant and influential topics in people's lives. Socially forbidden topics are among the controversial and unspoken subjects in society. This research addresses these topics in television series and their directorial treatments. Therefore, the research is titled "The Directorial Treatment of Socially Forbidden Topics in Television Series." The research consists of a summary and five chapters. The first chapter provides a methodological framework that includes the research problem, formulated as the following question: What is the directorial treatment of socially forbidden topics in television series? It also covers the importance and necessity of the research, with the aim of uncovering the directorial treatment of these topics in television series. The second chapter (Theoretical Framework and Previous Studies) contains two sections: the first addresses the term and concept of socially forbidden topics, while the second section discusses the directorial treatment of the visual language elements in television series. The researcher derived several indicators, which were used as tools for sample analysis. The third chapter outlines the research procedures, including the descriptive methodology, research population, and sample, which is the series "Forbidden Love." The fourth chapter analyzes the sample, and the fifth chapter presents the findings, conclusions, recommendations, and suggestions. The research concludes with references and a summary in EnglishConclusions:The inclusion format plays a prominent role in television drama.The dramatic structure of the television series employed sub-narrative methods to support the narrative structureCamera movements and shot sizes played into framing the directorial treatment of the television series4. The expressive use of color and lighting in television drama works to highlight the psychological states of people.